The Roles of Multicultural Islamic Education in The Empowerment of Civil Society - Shobirin, Muhammad Yusuf (JURNAL PENELITIAN KEISLAMAN, 2023)
Indonesia’s national identity is shaped by its diverse cultural tapestry, which embodies a rich historical legacy. While this diversity is a source of pride, it can also pose challenges that may lead to societal discord. Therefore, Islamic Education rooted in Multiculturalism is vital in fostering unity amidst diversity. Within this framework, Islamic Education plays a crucial role in harmonizing differences and shaping successive generations. By fostering appreciation for diversity and promoting solidarity, it bridges societal gaps and fosters a sense of belonging among Indonesians. Through Islamic teachings, this paradigm values diversity as a unifying force, fostering a society where differences strengthen unity. This approach aims to foster a population that values mutual respect, cooperation, and national unity, regardless of cultural differences. Therefore, Islamic Education within Multiculturalism aims to shape a generation that values diversity while also strengthening the nation's unity and integrity.